The Effect of the School Environment on Students’ Character Formation in PPKn Class IV Students at SD Negeri 101213 Baringin - Agnes Jenita Ginting; Fetti Sakinah Rangkuti; Nazuani Husna; Salsa Bella Anggina; Laurensia M. Perangin Angin (Journal of Educational Analytics, 2023)
Education is process, which is intertwined with the existence of the individual and society. Students are anticipated to grow in character as a result of continuous character development. Students with strong character are able to identify values and norms that are beneficial for their school. Specifically, educational setting effects to development of character in third-grade pupils at SDN 101213 Baringin. An empirical quantitative research methodology was applied. Questionnaires for observation and documentation were used as data collecting approaches. The traditional assumption test, hypothesis testing, and coefficient of determination test are analysis techniques employed (R2). The impact of the school environment on character and the existence of this relationship are positively and significantly related. This should be the instructor's first priority in terms of leading, managing, and caring for the kids.